2021
DOI: 10.1111/anu.13269
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of Superworm ( Zophobas morio ) larval meal as a partial protein source in experimental diets for juvenile Asian sea bass, Lates calcarifer

Abstract: A 12-week feeding trial with Asian sea bass Lates calcarifer juveniles was conducted to evaluate the response of feeding defatted Superworm (Zophobas morio) larval meal on growth performance, feed utilization, apparent digestibility coefficient of nutrients and haemato-biochemical status for Asian sea bass. Five isonitrogenous (450 g/kg) and isolipidic (125 g/kg) experimental diets were formulated. A basal diet that contained no insect meal from defatted Superworm (DFSM) served as the control. Four diets were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
2
9
1
Order By: Relevance
“…From each replicate, 5 fish were randomly weighed at the end of the trial to calculate growth performance, feed utilization, and biometric indices. Final body weight (FBW, g), weight gain (WG, g), specific growth rate (SGR, %/day), feed conversion ratio (FCR, feed: gain), hepatosomatic index (HSI, %), and viscerosomatic index (VSI, %) were calculated using the following formulas as labeled beforehand by Prachom et al [ 43 ]: Weight Gain (WG, g fish −1 ) = FW − IW where Ln and t are t natural logarithmic and time in days, respectively. Hepatosomatic index (HSI, %) = liver weight/body weight × 100 Viscerosomatic index (VSI, %) = visceral weight/body weight × 100 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From each replicate, 5 fish were randomly weighed at the end of the trial to calculate growth performance, feed utilization, and biometric indices. Final body weight (FBW, g), weight gain (WG, g), specific growth rate (SGR, %/day), feed conversion ratio (FCR, feed: gain), hepatosomatic index (HSI, %), and viscerosomatic index (VSI, %) were calculated using the following formulas as labeled beforehand by Prachom et al [ 43 ]: Weight Gain (WG, g fish −1 ) = FW − IW where Ln and t are t natural logarithmic and time in days, respectively. Hepatosomatic index (HSI, %) = liver weight/body weight × 100 Viscerosomatic index (VSI, %) = visceral weight/body weight × 100 …”
Section: Methodsmentioning
confidence: 99%
“…Briefly, after one month of feeding, the fecal samples were collected by hand siphoning from each aquarium every morning before the start of feeding. The feces were collected on filter paper for drying according to the protocol of Prachom et al [ 43 ]. The collected feces were dried in an oven at 50 °C for about 24 h and stored at −20 °C [ 44 ] until further chemical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…(2018) Butter catfish ( Ompok pabda ) 0.6 Earthworm meal ( Perionyx excavates ) Boiled, oven-dried, and ground 260.4 g/kg (75%) 8 wk Chakraborty et al. (2021) Asian sea bass ( Lates calcarifer ) 12.52 ± 0.52 Defatted superworm larvae ( Zophobas morio ) Ground, defatted, oven-dried, and reground 120 g/kg (44%) 12 wk Prachom et al. (2021) Mozambique tilapia ( Oreochromis mossambicus ) 40 ± 2.5 Mopane worm ( Imbrasia belina ) Gutted, cooked in brine & sundried 24 g/kg (60%) 51 d Rapatsa and Moyo (2017) African catfish ( Clarias gariepinus ) 4.00 ± 0.8 Field cricket ( Gryllus bimaculatus ) meal Oven-dried and ground 300 g/kg (100%) 56 d Taufek et al.…”
Section: Insect Biomass Production and Processing For Aquafeedmentioning
confidence: 99%
“…Many studies have already observed the influence of a TM-enriched diet on growth performances, weight gain and feed efficiency of broilers, laying hens and fish, where it was found that with proper diet composition, TM could be used as an alternative protein source [9,10,14]. One of the more recently investigated insects with great nutritional potential for future use as an alternative feedstuff is Zophobas morio (ZM), also known as super worm [15,16]. Female ZM lay more than 2000 eggs, and rearing conditions are very similar to TM, but reliable scientific data regarding its mass production are still largely lacking [16].…”
Section: Introductionmentioning
confidence: 99%
“…One of the more recently investigated insects with great nutritional potential for future use as an alternative feedstuff is Zophobas morio (ZM), also known as super worm [15,16]. Female ZM lay more than 2000 eggs, and rearing conditions are very similar to TM, but reliable scientific data regarding its mass production are still largely lacking [16]. Likewise, to the authors' best knowledge, published data on the nutritive evaluation of ZM and its integration into the diet of various animal species is still limited.…”
Section: Introductionmentioning
confidence: 99%